Own Waves in a Cylindrical Shell in Contact with a Viscous Liquid (Global Journal of Science Frontier Research, 2018)
Abstract not found
Keywords: the cylindrical shell; viscous barotropic liquid; wave process; dissipative non-uniform; wavy motion